2016
DOI: 10.1111/mmi.13311
|View full text |Cite
|
Sign up to set email alerts
|

The SpoIIQ‐SpoIIIAH complex of Clostridium difficile controls forespore engulfment and late stages of gene expression and spore morphogenesis

Abstract: SummaryEngulfment of the forespore by the mother cell is a universal feature of endosporulation. In Bacillus subtilis, the forespore protein SpoIIQ and the mother cell protein SpoIIIAH form a channel, essential for endosporulation, through which the developing spore is nurtured. The two proteins also form a backup system for engulfment. Unlike in B. subtilis, SpoIIQ of Clostridium difficile has intact LytM zinc‐binding motifs. We show that spoIIQ or spoIIIAH deletion mutants of C. difficile result in anomalous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 65 publications
(217 reference statements)
1
73
0
Order By: Relevance
“…While our 630∆ erm ∆ spoIIQ strain generated heat‐resistant spores less efficiently than wildtype (~0.05%), loss of IIQ in this strain background has been previously reported to prevent heat‐resistant spore formation (Dembek et al ., ; Serrano et al ., ). This discrepancy is likely due to differences in the sporulation method used (plate‐based vs. liquid), since comparison of the heat resistance of sporulating ∆ IIQ in liquid vs. plate culture revealed a 20‐fold more severe defect during growth in broth with agitation relative to growth on plates (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…While our 630∆ erm ∆ spoIIQ strain generated heat‐resistant spores less efficiently than wildtype (~0.05%), loss of IIQ in this strain background has been previously reported to prevent heat‐resistant spore formation (Dembek et al ., ; Serrano et al ., ). This discrepancy is likely due to differences in the sporulation method used (plate‐based vs. liquid), since comparison of the heat resistance of sporulating ∆ IIQ in liquid vs. plate culture revealed a 20‐fold more severe defect during growth in broth with agitation relative to growth on plates (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, recent work in the endospore former Clostridium difficile suggests that the A-Q complex may be dispensable for late forespore gene expression under SigG control and therefore may not play a direct role in maintaining transcriptional potential in the C. difficile forespore (8,9). Intriguingly, both studies identified morphological defects in spore differentiation in the absence of the A-Q complex, suggesting that the complex could play a structural role in maintaining forespore development.…”
Section: Discussionmentioning
confidence: 99%
“…1B) (3). Intriguingly, the mother cell and forespore assemble a multimeric complex spanning these two membranes that bears similarity to specialized secretion systems and is required to maintain forespore development (4)(5)(6)(7)(8)(9). It has been proposed that these proteins constitute a hybrid specialized secretion system with a channel connecting mother cell and forespore.…”
mentioning
confidence: 99%
“…For instance, the SpoIIQ-AH zipper, which is dispensable for engulfment in native conditions (Broder and Pogliano, 2006), might prevent membrane backward movement, and might also help localize the IDC components toward the LE. Interestingly, SpoIIQ-AH interaction is essential for engulfment in Clostridium difficile where the SpoIIQ ortholog posseses endopeptidase activity (Crawshaw et al, 2014; Serrano et al, 2016; Fimlaid et al, 2015). The model also does not consider the impact of the tethering of the LE of the engulfing membrane to the forespore via interactions between the mother cell membrane anchored DMP complex at the LE and forespore synthesized PG.…”
Section: Discussionmentioning
confidence: 99%